Development of The Technical University Students' Civic Consciousness. (13th May 2015) - Valeeva, Roza A.; Koroleva, Natalya E.; Sakhapova, Farida Kh.
Abstract: The article is devoted to the theoretical background and techniques of the youth civic education and discloses the problems of students' civic consciousness and civic qualities formation. The aim of the article is founding out the ways of the educational work efficiency in foreign language classes in high school for the Technical University Students' civic consciousness development. It is confirmed that civic education is closely connected with the historical changes in Russia that require educating a new person able to realize the interests of the state. This makes it necessary to identify and study the content, objectives, forms and methods of Technical University Students' civic consciousness improvement. The results of the definition and specification of the notion of "civic education" also introduced in the article.